PENINGKATAN KETERAMPILAN MENGKOMUNIKASIKAN DAN PENCAPAIAN KOMPETENSI SISWA MENGGUNAKAN MODEL PEMBELAJARAN LEARNING CYCLE 3E - Nurul Insani; Emmawaty Sofya; Tasviri Efkar (Jurnal Pendidikan dan Pembelajaran Kimia, 2013)
The aim of this research is to describe the effectiveness of learning cycle 3E  learning models is improving the skills of communicating and achievements competence students for reaction chemical equilibrium competence. Learning cycle 3E models is learning through a series of stages (phases of learning) learning phases include: (1) the exploration phase, (2) explanation of the concept phase, and (3) the application of the concept phase. This study used a quasi-experimental method with Non Equivalent (Pretest and Posttest) Control Group Design. Effectiveness of the learning cycle 3E models is measured by an increase in competence by KKM and      n-gain significant.  The results showed an increase in competence for the control and experimental classes respectively 33.3% and 66.7% and the mean n-gain the skills to communicating at experimental classes and control classes respectively 0.41 and 0.56 and the mean n-gain achievements competence for and experimental classes and control classes respectively 0.47 and 0.64  Thus, it can be conclud that the learning cycle 3E learning model on reaction chemical equilibrium material effectives to enhance communicating skill and achievements competence of students in medium category.Kata kunci: learning cycle 3e, keterampilan mengkomunikasikan, pencapaian kompetensi siswa.